Pengaruh Petugas Tidak Resmi Terhadap Lalu Lintas Pada Simpang Tiga Bersinyal di Jl. Kaliurang KM.8 Yogyakarta - Prima Romadhona; Umi Nur Chasanah (Jurnal Teknik Sipil dan Lingkungan, 2020)
The congestion at the PLN intersection Kaliurang street Km 8 is the reason of Unofficial Officers or so-called "Pak Ogah" act as traffic regulators or assist in the movement of driving from minor roads to major roads. Therefore, the objective of the study was to determine the impact of Unofficial Officers on the performance of intersections. The survey was conducted for 3 days which were volume survey, a survey of vehicle speed, driving behavior, and length of the queue. VISSIM modeling analysis results showed that using signals was better than existing conditions with a decrease in the average delay value of 18.44% and a decrease in the average queue length of 80.34%. Meanwhile, the condition of intersections with unofficial officers decreased by an average delay of 22.10% compared to existing conditions. However, the average queued length by unofficial officers increased by 22.54% compared to existing conditions. Although the results of delays with Unofficial Officers were better than other conditions, arrangements by unofficial officers had many conflicts, creating the risk of accidents at the intersection.